Epithelial mesenchymal transition in human menstruation and implantation - Hiroshi Uchida (Endocrine Journal)
The endometrium during the sexual cycle undergoes detachment, tissue remodeling, and differentiation during the menstrual cycle. Localized and transient destruction and regeneration of endometrial tissue are also essential for pregnancy. It is possible to attribute many causes of failure in infertility treatment to the implantation stage. To improve the success rate of plateau fertility treatment, it is important to understand the regeneration mechanism of the endometrium, a unique regenerative tissue in the human body. In association with cell proliferation, tissue remodeling requires the relocation of proliferative cells, and the steady-state epithelial cells need to be motile for the relocation. Transient add-on motile activity in epithelial cells is mediated by epithelial to mesenchymal transition (EMT) and reversible mesenchymal to epithelial transition (MET). The destruction and regeneration of endometrial tissue over a period of days to weeks requires a system with a rapid and characteristic mechanism similar to that of wound healing. Here, I review the relationship between the well-known phenomenon of EMT in wound healing and endometrial tissue remodeling during the sexual cycle and pregnancy establishment, which are automatically triggered by menstruation and embryonal invasion.